Discovering atomistic pathways for supply of metal atoms from methyl-based precursors to graphene surface. Issue 1 (13th December 2022) - Sangiovanni, Davide G.; Faccio, Ricardo; Gueorguiev, Gueorgui Kostov; Kakanakova-Georgieva, Anelia
Abstract : Schematic illustration of precursors and reaction products of simulated MOCVD of Trimethyl-Indium on graphene. Abstract : Conceptual 2D group III nitrides and oxides ( e.g., 2D InN and 2D InO) in heterostructures with graphene have been realized by metal–organic chemical vapor deposition (MOCVD). MOCVD is expected to bring forth the same impact in the advancement of 2D semiconductor materials as in the fabrication of established semiconductor materials and device heterostructures. MOCVD employs metal–organic precursors such as trimethyl-indium, -gallium, and -aluminum, with (strong) metal–carbon bonds. Mechanisms that regulate MOCVD processes at the atomic scale are largely unknown. Here, we employ density-functional molecular dynamics – accounting for van der Waals interactions – to identify the reaction pathways responsible for dissociation of the trimethylindium (TMIn) precursor in the gas phase as well as on top-layer and zero-layer graphene. The simulations reveal how collisions with hydrogen molecules, intramolecular or surface-mediated proton transfer, and direct TMIn/graphene reactions assist TMIn transformations, which ultimately enables delivery of In monomers or InH and CH3 In admolecules, on graphene. This work provides knowledge for understanding the nucleation and intercalation mechanisms at the atomic scale and for carrying out epitaxial growth of 2D materials and graphene heterostructures.